The use of small molecules in somatic-cell reprogramming - Federation, Alexander J. (2013)
Pioneering work over the past years has highlighted the remarkable ability of manipulating cell states through exogenous, mostly transcription factor-induced reprogramming. The use of small molecules and reprogramming by transcription factors share a common history starting with the early AZA and MyoD experiments in fibroblast cells. Recent work shows that a combination of small molecules can replace all of the reprogramming factors and many previous studies have demonstrated their use in enhancing efficiencies or replacing individual factors. Here we provide a brief introduction to reprogramming followed by a detailed review of the major classes of small molecules that have been used to date and what future opportunities can be expected from these.